2022
DOI: 10.1037/rev0000334
|View full text |Cite
|
Sign up to set email alerts
|

A memory-based theory of emotional disorders.

Abstract: Learning and memory play a central role in emotional disorders, particularly in depression and posttraumatic stress disorder. We present a new, transdiagnostic theory of how memory and mood interact in emotional disorders. Drawing upon retrieved-context models of episodic memory, we propose that memories form associations with the contexts in which they are encoded, including emotional valence and arousal. Later, encountering contextual cues retrieves their associated memories, which in turn reactivate the con… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

7
18
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(44 citation statements)
references
References 160 publications
7
18
0
1
Order By: Relevance
“…Our findings suggest an alternative and complementary path for emotion-temporal coding interactions: high-fidelity temporal memory may potentially protect (or rescue) emotional experiences from retrospective biases indicative of temporal neglect-preventing emotion-driven distortions in retrospective evaluative judgments. While future research using causal methods is required to fully ascertain directionality in emotion-temporal interactions, our results add to a growing literature underscoring critical (and likely bidirectional) interactions of emotion and temporal memory (Cohen & Kahana, 2022;Lapate et al, 2017;Palombo et al, 2021;Palombo & Cocquyt, 2020;Petrucci & Palombo, 2021;Talmi et al, 2019).…”
Section: Temporal Duration Errormentioning
confidence: 60%
See 1 more Smart Citation
“…Our findings suggest an alternative and complementary path for emotion-temporal coding interactions: high-fidelity temporal memory may potentially protect (or rescue) emotional experiences from retrospective biases indicative of temporal neglect-preventing emotion-driven distortions in retrospective evaluative judgments. While future research using causal methods is required to fully ascertain directionality in emotion-temporal interactions, our results add to a growing literature underscoring critical (and likely bidirectional) interactions of emotion and temporal memory (Cohen & Kahana, 2022;Lapate et al, 2017;Palombo et al, 2021;Palombo & Cocquyt, 2020;Petrucci & Palombo, 2021;Talmi et al, 2019).…”
Section: Temporal Duration Errormentioning
confidence: 60%
“…For instance, the duration of negative events is typically subjectively dilated in retrospective estimates (Campbell & Bryant, 2007;Johnson & MacKay, 2019;Loftus et al, 1987;Stetson et al, 2007). Moreover, emotional items can disrupt chronologically organized free recall, producing emotion-driven clustering in memory retrieval (Cohen & Kahana, 2022;Talmi et al, 2019). Temporal order memory has likewise been found to be altered by high-arousal negative emotion (impaired: Huntjens et al, 2015;Maddock & Frein, 2009;and enhanced: Dev et al, 2022;Schmidt et al, 2011).…”
Section: Introductionmentioning
confidence: 99%
“…Persistence is characterized by the presence of unwanted and emotionally arousing intrusive memories, typically resulting from disturbing or traumatic events, that produce negative effects on psychological well-being and are sometimes associated with clinical psychopathology, such as posttraumatic stress disorder (PTSD; see Brewin et al, 2010, for review). Recent years have witnessed considerable progress in understanding the nature and basis of such intrusive memories (e.g., Cohen & Kahana, 2022; Iyadurai et al, 2018). Most relevant to the present concerns, there has also been impressive progress in applying insights from basic research to the treatment of intrusive memories in clinical settings (Iyadurai et al, 2019; Phelps & Hofmann, 2019).…”
Section: Persistencementioning
confidence: 99%
“…As we noted earlier, we have in previous work demonstrated that the imagery-competing task intervention is successful in reducing intrusion rates while leaving factual and/or episodic components of the memory intact for voluntary retrieval (Lau-Zhu et al, 2019, 2021), consistent with dual representation accounts of intrusive memories (Brewin et al, 2010). This, however, leaves open the question of what precise features of the memories are being diminished (e.g., sensory–perceptual features), when they are transformed into a nonintrusive state, and how this relates to theoretical accounts on the basis of memory intrusions (e.g., Bisby et al, 2020; Brewin et al, 2010; Cohen & Kahana, 2022; Ehlers & Clark, 2000). Moving forward, it will be important to develop measures to assess underlying changes to these memories in order to examine the proposal that successful treatment of intrusive memories may be a function of targeting and diminishing sensory–perceptual features.…”
Section: Two Seals About Measuring Intrusionsmentioning
confidence: 99%